1999
DOI: 10.1038/10579
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Calpain 3 deficiency is associated with myonuclear apoptosis and profound perturbation of the IkBa/NF-kB pathway in limb-girdle muscular dystrophy type 2A

Abstract: Calpain 3 deficiency is associated with myonuclear apoptosis and profound perturbation of the IkBa/NF-kB pathway in limb-girdle muscular dystrophy type 2A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 1 publication
2
65
0
5
Order By: Relevance
“…34,35 Calpain 3 deficiency is associated with myonuclear apoptosis possibly due to inability to degrade IkBa. 36 Furthermore, calpain-independent cell death was also observed in thymocyte triggered by heat shock and by valinomycin and in cultured rat cardiomyocytes during metabolic inhibition. 21,37 Thus, the role of calpain in apoptosis is controversial and depends on cell types and treatment.…”
Section: Introductionmentioning
confidence: 92%
“…34,35 Calpain 3 deficiency is associated with myonuclear apoptosis possibly due to inability to degrade IkBa. 36 Furthermore, calpain-independent cell death was also observed in thymocyte triggered by heat shock and by valinomycin and in cultured rat cardiomyocytes during metabolic inhibition. 21,37 Thus, the role of calpain in apoptosis is controversial and depends on cell types and treatment.…”
Section: Introductionmentioning
confidence: 92%
“…The mechanisms by which reovirus triggers increased cellular calpain activity are not known but may include initiation of calcium fluxes following viral attachment, as demonstrated with rotavirus, a closely related virus (15); upregulation of growth factors which facilitate calpain activation (37,66); or upregulation of endogenous calpain activator proteins which have been characterized for several cell types (49). Calpain may play a physiologic role in the regulation of a variety of cellular transcription factors and cell cycle-regulating factors implicated in apoptosis, including Jun, Fos, p53, cyclin D, and NF-B (3,7,73). We have recently shown that activation of NF-B is required for reovirus-induced apoptosis (J. L. Connolly, S. E. Rodgers, B. Pike, P. Clarke, K. L. Tyler, and T. S. Dermody, Abstr.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its nuclear localization signal sequence, calpain-3 might act in the nucleus in particular conditions and might be involved in the regulation of transcription factors controlling survival genes and apoptosis. 15,16 Several molecules with regulatory functions have been reported to be substrates for calpains in cell culture, but various lines of research have suggested that calpains may be involved in cytoskeletal or myofibrillar protein degradation. 5,17,18 While it is unlikely that calpain-3 is implicated in myoblast fusion, being fusion-effective in muscle of LGMD2A patients, it might act in the disassembly of myofibrils during early stages of turnover 17 or cause a postfusion defect in muscle maturation.…”
mentioning
confidence: 99%